A new approach for the shaping up of very fine and beadless UV light absorbing polycarbonate fibers by electrospinning. (December 2019) - Baby, Thomas; Jose E, Tomlal; George, Gejo; Varkey, Vinitha; Cherian, Shijo K.
Abstract: An innovation will be recognized as successful only if it satisfies all phases of product development; i.e. from the specification to mass production. Therefore, a cost-effective production by keeping the best possible characteristics is vital in any Industry. Large scale production of polymer fibers with ultrafine morphology is such a challenge to the field of nanotechnology. The idea proposed here utilizes the versatile electrospinning technology for the preparation of uniform, beadless and ultraviolet light absorbing polycarbonate (PC) nanofibers. The average diameter limits to 114 nm and that too by using most convenient and comparatively less toxic solvent mixture. This method is simple and so far, it is not reported elsewhere. For THF-DMF system a PC concentration of 17 w/v% and for DCM-DMF system a PC concentration of 15 w/v% was found to be the optimum polymer concentration. The average fiber diameter and bead density were very much influenced by the viscosity, conductivity and concentration of the solution used for electrospinning. The PC fibers (PC concentration of 15 w/v % in DCM-DMF system) with lowest average diameter of 114 nm shows excellent ultraviolet absorption, semicrystalline nature, enhanced glass transition temperature and thermal stability. Highlights: Electrospinning method was adopted to prepare uniform bead free PC nanofibers using two solvent mixtures in a systematic way. Bead free PC fibers with least average diameter of 114 nm was obtained for a 15 w/v % solution in 1:1 DCM - DMF mixture. The PC nanofibers with least average diameter exhibited excellent ultraviolet absorption, semicrystalline nature and improved glass transition temperature. The bead density, surface morphology and average fiber diameter were influenced by various spinning parameters. This method proposes the minimum use of materials including comparatively less toxic solvents for the preparation of PC nanofibers.